2021
DOI: 10.1001/jamahealthforum.2021.1719
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Hospital-Acquired Conditions Associated With Potential Low-Value Care in Medicare Beneficiaries

Abstract: IMPORTANCE There has been insufficient research on the patient harms and costs associated with potential low-value procedures in the US Medicare population. OBJECTIVE To report the prevalence of adverse events associated with potential low-value procedures and the additional hospital length of stay (LOS) and costs. DESIGN, SETTING, AND PARTICIPANTS This is a retrospective cohort study using Medicare fee-for-service claims between January 2016 to December 2018. Participants were aged 65 years or older. Procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Recently published studies examined the downstream effects of low-value care procedures in hospitals. They revealed that patients who received low-value care were associated with higher Medicare costs and longer lengths of stay [ 40 , 41 ], which is in line with the results of our analysis, demonstrating that PwD who received Lvm treatments were more frequently hospitalized (39 vs 26%) and stayed longer in hospitals (6 vs 3 days). The higher utilization of in-hospital services resulted in higher inpatient treatment costs (4501 € vs 2380 €) compared with PwD without Lvm treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Recently published studies examined the downstream effects of low-value care procedures in hospitals. They revealed that patients who received low-value care were associated with higher Medicare costs and longer lengths of stay [ 40 , 41 ], which is in line with the results of our analysis, demonstrating that PwD who received Lvm treatments were more frequently hospitalized (39 vs 26%) and stayed longer in hospitals (6 vs 3 days). The higher utilization of in-hospital services resulted in higher inpatient treatment costs (4501 € vs 2380 €) compared with PwD without Lvm treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Recently published studies examined the downstream effects of low-value care procedures in hospitals. They revealed that patients who received low-value care were associated with higher Medicare costs and longer lengths of stay [40,41], which is in line with the results of our analysis, demonstrating that PwD who received Lvm treatments were more frequently hospitalized (39 vs 26%) and stayed longer in hospitals (6 vs 3 days). The higher utilization of in-hospital services resulted in higher inpatient treatment costs (4501 € vs 2380 €) compared with PwD without Lvm treatments.…”
Section: Discussionsupporting
confidence: 89%
“…The extent and number of LVPs and their economic impact have been studied for years in various countries and healthcare levels [ 10 , 35 , 36 ]. Some recent studies have emerged identifying the impact of LVPs in terms of patient safety, linking LVPs to the occurrence of preventable adverse events [ 37 ].…”
Section: Discussionmentioning
confidence: 99%